The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1016/s0899-3467(07)60152-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic low back pain incorporating active patient participation and chiropractic: a retrospective case report

Abstract: (J Chiropr Med 2005;4:200-205)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…An unique finding of the present study was that tennis induces an asymmetric hypertrophy of iliopsoas and gluteal muscles and soccer compensates the asymmetry observed in non-active controls. It remains to be determined whether these different patterns can modify the risk of lower back pain and chronic groin pain [6] , [13] , [14] , [43] . Moreover, the low magnitude of hypertrophy of gluteal muscles observed in our soccer players could be associated to a greater risk of anterior cruciate ligament injuries [22] , [44] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An unique finding of the present study was that tennis induces an asymmetric hypertrophy of iliopsoas and gluteal muscles and soccer compensates the asymmetry observed in non-active controls. It remains to be determined whether these different patterns can modify the risk of lower back pain and chronic groin pain [6] , [13] , [14] , [43] . Moreover, the low magnitude of hypertrophy of gluteal muscles observed in our soccer players could be associated to a greater risk of anterior cruciate ligament injuries [22] , [44] .…”
Section: Discussionmentioning
confidence: 99%
“…A study using electromyography showed that the iliopsoas of the dominant leg (the preferred leg to kick the ball) was the most active muscle during the entire kicking motion whilst gluteus maximus was moderately active during the acceleration phase of the kicking leg and increased its activity just before ball impact [12] . Iliopsoas and gluteal muscles are also very demanded in tennis [13] , [14] . Studies using cinematography have shown that the players profit the linear momentum from the extension of the lower extremities to asymmetrically activate lower trunk muscles to produce power during tennis strokes [15] [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the use of ozone in general medicine include treatment of back pain, a condition that affects up to 80% of the world's population [11][12][13]. Dr. A. Balkanyi in Zurich is believed to have been the first to treat patients with pain caused by tendinitis and myofascial pain by injecting small amounts of ozone [14][15][16].…”
Section: Introductionmentioning
confidence: 99%